The impact of product variety on fill rate, inventory and sales performance in the consumer goods industry. Issue 7 (22nd April 2020) - Santos, Victor; Sampaio, Mauro; Alliprandini, Dario Henrique
Abstract : Purpose: The impact of product variety decisions on fill rate, inventory and sales performance in a consumer goods company has been examined. From a marketing perspective, it is possible to leverage sales, reach new segments and consequently increase competitiveness when there is a greater product variety on the market. However, operations and logistics professionals indicate potential impacts on the supply chain, such as production, storage and distribution complexity. The nature of the product variety-cost-sales performance relationship is not clear, and empirical evidence about whether and how operations cost and sales performance increases with variety is inconclusive. Design/methodology/approach: The multiple linear regression and the Tobit regression techniques were applied over a seven-year horizon of data from a business intelligence platform of a consumer goods company. Findings: Our results show that sales performance is negatively associated with product variety. The total effect of product variety on sales performance has been examined, including both the direct effect and the indirect effect through inventory and fill rate. Therefore, the findings provide a comprehensive understanding of the impact of product variety on operations and sales performance. Originality/value: Several studies have researched the impact of product variety on fill rate, inventory and sales performance separately; however, the research of the impact and the relationship of these factors is scarce and limited.